THE HISTORICAL ASPECT OF DUAL CAREER IN EU AND GROWTH OPPORTUNITIES IN LATVIA - Ābele, Agita; Abelkalns, Ilvis; Liduma, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
From the information of organisations EUSA (2020), EAS (2022) and FISU (2022) documents, it is indicated that dual careers have been one of the priorities at the EU level in the last decade. Today's complex conditions in the world and in Latvia require paying more attention to Dual career support for student-athletes. Mentor support centres are being created for this in the world. There is no such centre in Latvia yet. The time of an athlete's career is short, so support is needed for students-athletes both for successful studies and high sports achievements.The purpose of the article is to explore the historical formation and growth opportunities of Dual Career in Latvia.Materials and methods. Theoretical method – Analysis of theoretical sources and documents. The study analyses Dual career terminology, historical formation in the world and Dual career opportunities in Latvia. The support of University Sports Centres and mentor centre is needed to provide up-to-date information to student-athletes. Important information for the creation of a dual career centre is identified Within the framework of FISU-NUSF Projects 2022 – Establishment of a Dual Career Mentor Centre in Latvia.